Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Reptile responses to anthropogenic habitat modification: A global meta‐analysis - Tim S. Doherty; Sara Balouch; Kristian Bell; Thomas J. Burns; Anat Feldman; Charles Fist; Timothy F. Garvey; Tim S. Jessop; Shai Meiri; Don A. Driscoll (Global Ecology and Biogeography, 2020)
Aim The aim was to determine how reptile populations respond to anthropogenic habitat modification and determine whether species traits and environmental factors influence such responses. Location Global. Time period 1981–2018. Major taxa studied Squamata. Methods We compiled a database of 56 studies reporting how habitat modification affects reptile abundance and calculated standardized mean differences in abundance (Hedges’ g ). We used Bayesian meta‐analytical models to test whether responses to habitat modification depended on body size, clutch size, reproductive mode, habitat specialization, range size, disturbance type, vegetation type, temperature and precipitation. Results Based on 815 effect sizes from 376 species, we found an overall negative effect of habitat modification on reptile abundance (mean Hedges’ g = −0.43, 95% credible intervals = −0.61 to −0.26). Reptile abundance was, on average, one‐third lower in modified compared with unmodified habitats. Small range sizes and small clutch sizes were associated with more negative responses to habitat modification, although the responses were weak and the credible intervals overlapped zero. We detected no effects of body size, habitat specialization, reproductive mode (egg‐laying or live‐bearing), temperature or precipitation. Some families exhibited more negative responses than others, although overall there was no phylogenetic signal in the data. Mining had the most negative impacts on reptile abundance, followed by agriculture, grazing, plantations and patch size reduction, whereas the mean effect of logging was neutral. Main conclusions Habitat modification is a key cause of reptile population declines, although there is variability in responses both within and between species, families and vegetation types. The effect of disturbance type appeared to be related to the intensity of habitat modification. Ongoing development of environmentally sustainable practices that ameliorate anthropogenic impacts is urgently needed to prevent declines in reptile populations.

A critique of 'countryside biogeography' as a guide to research in human‐dominated landscapes - Don A. Driscoll; Sara Balouch; Thomas J. Burns; Tim F. Garvey; Tricia Wevill; Kaori Yokochi; Tim S. Doherty (Journal of Biogeography, 2019)
Proliferation of redundant terms in ecology and conservation slows progress and creates confusion. ‘Countryside biogeography’ has been promoted as a new framework for conservation in production landscapes, so may offer a replacement for other concepts used by landscape ecologists. We conducted a systematic review to assess whether the 'countryside biogeography' concept provides a distinctive framing for conservation in human‐dominated landscapes relative to existing concepts. We reviewed 147 papers referring to countryside biogeography and 81 papers that did not. These papers were divided into categories representing three levels of use of countryside biogeography concepts (strong, weak, cited only) and two categories that did not use countryside biogeography at all but used similar concepts including fragmentation and matrix. We revealed few distinctions among groups of papers. Countryside biogeography papers made more frequent use of the terms 'ecosystem services', 'intensification' and 'land sparing' compared with non‐countryside biogeography papers. Papers that did not refer to countryside biogeography sampled production areas (e.g. farms) less often, and this related to their focus on habitat specialist species for which patch‐matrix assumptions were reasonable. Countryside biogeography offers a conceptual wrapper rather than a distinctive framework for advancing research in human‐modified landscapes. This and similar wrappers such as ‘conservation biogeography’ and ‘agricultural biogeography’ risk creating confusion among new researchers, and can prevent clear communication about research. To improve communication, we recommend using the suite of well‐established terms already applied to conservation in human‐modified landscapes rather than through an interceding conceptual wrapper.